Synchronous rectification of LLC resonant converters based on resonant inductor voltage - Luo, Zuohao; Wu, Zaijun; Quan, Xiangjun; Xie, Xingfeng; Dou, Xiaobo; Hu, Qinran (Frontiers in Energy Research, 2023)
Synchronous rectification (SR) technology has been a critical technology for LLC converters to achieve high efficiency and power density. However, conventional SR driving methods face challenges in terms of light-load condition, module size, switching accuracy, and circuit complexity. This paper proposes an SR driving strategy based on resonant inductor voltage (RLV) to address those issues. This RLV SR driving strategy does not require current sensors and is insensitive to rectifier parasitic parameters. In addition, the RLV SR driving strategy can be applied in a relatively wide operating frequency range and load conditions. Experimental results based on a 100-W/24-V LLC converter are presented to verify the effectiveness of the proposed RLV SR driving strategy. Furthermore, the error of turn-on time caused by stray inductance is significantly reduced compared with the conventional VDS-ON sensing method, which improves the power converter’s efficiency.